Trade, Trees, and Contingent Trade Agreements - Bård Harstad (Center for Economic Studies and ifo Institute (CESifo), 2022)
Can trade agreements motivate environmental conservation? I first present a model whereby the government in the South expands its production capacity (e.g., deforest) before trading with the North. After deriving negative relationships between tariff reductions and conservation, I show how all negative results are reversed if countries can negotiate a contingent trade agreement (CTA), where default tariffs vary with changes in the production capacity (or forest cover). A calibration suggests that growth and liberalization can cause Brazil's agricultural area to expand by 27%, but this expansion can be avoided if the EU and the US offer a CTA.
Keywords: F18; F13; F550Q560; Q37; 330; international trade; trade agreements; deforestation; environmental conservation